Omer Lutfi Pasha in Bosnia - Temizer, Abidin (Historical Thought, 2025)
Omer Lutfi Pasha was born in 1806 in Janja Gora in Croatia. His parents were Orthodox Christians. However, he converted to Islam when he fled to Bosnia. After then he joined the Ottoman army. Omer Lutfi Pasha crushed several rebellions and was a commander of many wars throughout the Ottoman Empire. He was commander in Lebanon (1842), Albania (1843), Kurdistan (1846), Bosnia (1850), Montenegro (1852 and 1862), Oltenita (1853), Slistra and Bucharest (1854), Crimea (1855) and Baghdad (1857-1859). This article examines the data from the Ottoman Archives documents related to his activities in Bosnia and Herzegovina. In particular, we will refer to the activities of Omer Pasha on reforms, as it is known that he crushed the resistance in Bosnia to the Ottoman reforms.